Determinants of Debt Policy in Indonesia’s Manufacturing Companies - Natasha Claudia Darmawan; Liana Susanto (International Journal of Application on Economics and Business, 2023)
For manufacturing companies in Indonesia, the goal of this study is to gather empirical evidence to see if institutional ownership has a negative impact on corporate debt policy, if free cash flow has a negative impact on corporate debt policy, if asset structure has a positive impact on corporate debt policy, and if profitability has a negative impact on corporate debt policy. This study collects data using a purposive sample strategy and processes it using EViews 12 SV. Institutional ownership has no impact on corporate debt policy, free cash flow has a negative impact on corporate debt policy, asset structure has a negative impact on corporate debt policy, and profitability has a negative impact on corporate debt policy, according to research conducted on 73 companies between 2017 and 2020.